Influence of geological works on surface water and bottom sediments of Ayhalsky mining industry (Yakutia) (Proceedings of Voronezh State University. Series: Geology, 2019)
This work presents the results of studying the effect of geological work on surface water and bottom sediments of the Aikhal mining complex (GIC) as a typical object of geological exploration and mining activities in the permafrost zone. The main types of geological works that have a negative impact on the studied components of the environment in unique natural conditions are identified. Among them: prospecting, exploration, mining and processing work. The main polluting elements to which heavy metals (Zn, Li, Pb, Cu, washed out from the mining rocks) are attributed; sources of exposure represented by elements of the mining and processing industries. As environmental measures to minimize the negative impact on surface water and sediment proposed rational placement of culverts and devices during the construction of roads; location of transportation routes for drilling rigs and their movement during the period of conservation of the seasonally thawed layer; use of vertical planning with storm drains and elements of active drainage of permafrost drains; creation of artificial man-made geochemical barriers of carbonate or carbonate-clay type; correlation of drilling and blasting operations with weather conditions.
Keywords: surface water and bottom sediments; permafrost; the impact of exploration and mining activities; technogenesis; geological work; set of environmental measures for cryozone mining enterprises